Using action learning to tackle food insecurity in Scotland. (2nd January 2020) - Marshall, Chelsea; Cook, Ruth
ABSTRACT: In the context of a dramatic rise in food bank use in Scotland, the A Menu for Change project, delivered by Oxfam Scotland, Child Poverty Action Group in Scotland, Nourish Scotland and The Poverty Alliance, aimed to reduce the need for emergency food aid by improving local responses to food insecurity. Between 2017 and 2019, project officers worked with key stakeholders in Dundee City, East Ayrshire and Fife to identify and address challenges that people experiencing acute food insecurity face in accessing all the financial support and advice to which they are entitled. The project employed a cross-sectoral and multi-level approach in these three local authority areas. This account reviews the way action learning was used by the A Menu for Change project in Scotland, including an example of how one presentation led to practical changes in local referral patterns. The project demonstrated that action learning can be a useful approach for creating, supporting and developing relationships across complex systems and a mechanism for establishing the groundwork for social change. Facilitators learned that there is a need to work closely with stakeholders inside and outside the set to ensure the benefits of reflective learning influence policy and practice change.